Minutes of the 40th Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of Minutes of the 39th Meeting of the Academic Council. 2. Review the progress of implementation of decisions of the 39th Meeting of the Academic Council. 3. Approval of the Results of Spring 2010 Semester . 4. Approval of the Results of students graduating at the end of Fall 2010 Semester. 5. Approval of EEE Transcript Format. 6. Renumbering MS in Biotechnology courses. 7. Introduction of MS in Nuclear Science and Engineering. 8. Review the curriculum on "Minor in Investment Management". 9. Waiver Policy for EMBA Program. 10. Review of Code of Conduct on Drug related issues. 11. Review the approval of "Masters Programme on Purchasing and Supply Management".